Development and Perspectives of English, as a Language of Instruction and Learning in Chinese Educational System - Khan, Maria; Waheed, Misbah; Chengwen, Hong; Butt, Tahir Munir; Ahmad, Jamil (Asian Journal of Contemporary Education, 2018)
World has a new mania of ENGLISH learning. English as a language of learning or scholarly production and advanced studies, as well as the language of business and diplomacy has increased throughout the world but in China, its increasing trend as the language of instruction and learning in the last quarter century has received much more importance. Moreover, major developments and modifications in English language teaching have been made in last three decades. As we know, that China stood as political, social, most importantly economic and powerful socialist state throughout the world, due to the reason, Chinese leadership felt the need of the hour to have a grip on western languages especially English to compete with the contemporary super power countries. This review paper discusses a historical overview of Development and prospects of English, as language of Instruction and Learning, in Chinese Educational System and touches the present issues and trends. It originates that Chinese academia and students are giving much importance towards the communicative proficiency in their daily life. This scientific paper also dig out a logical finding that how Chinese educational System is evolving itself to meet up with the outer world and to open ways for their learners to utilize the opportunities in first world for the purpose of gaining English language proficiency.